THE INFLUENCE OF NON PHYSICAL WORK ENVIRONMENT AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE THROUGH ORGANIZATIONAL COMMITMENTS - Taufiqqurachman; Muhammad Firdaus; Muhaimin Dimyati (MBA - Journal of Management and Business Aplication, 2023)
The purpose of this study was to determine directly or indirectly the influence of the non-physical work environment and organizational culture on employee performance throughorganizational commitment as an intervening variable on employees of the Regional Secretariatof Bondowoso Regency. The number of samples in this study was 100 with purposive samplingtechnique. The analytical technique used is path analysis using SPSS 22.0. The results of dataanalysis show that the non-physical work environment has a significant effect on organizationalcommitment, organizational culture has a significant effect on organizational commitment,non-physical work environment has a significant effect on employee performance,organizational culture has a significant effect on employee performance, and organizationalcommitment has a significant effect on employee performance. Indirectly, the non-physicalwork environment and organizational culture have a significant effect on employeeperformance through organizational commitment.